2021
DOI: 10.1002/eqe.3474
|View full text |Cite
|
Sign up to set email alerts
|

Experimental testing of hybrid sliding‐rocking bridge columns under torsional and biaxial lateral loading

Abstract: Hybrid sliding-rocking (HSR) bridge columns are precast concrete segmental columns with unbonded posttensioning, end rocking joints, and intermediate sliding joints. Having been developed for construction in seismic regions, HSR columns offer self-centering, energy dissipation, and low damageability. Recent advances in the computational modeling of HSR columns have resulted in the proposal of a number of refinements to their original design, leading to the introduction of Second-Generation HSR columns. Compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 50 publications
(155 reference statements)
1
6
0
Order By: Relevance
“…Overall, it was found that the sliding between the segments significantly contributed to the energy dissipation of the column. Further study was carried out to investigate the seismic performance of the sliding-rocking columns under torsional and biaxial loading (Salehi et al 2021b).…”
Section: Rocking-sliding Column Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, it was found that the sliding between the segments significantly contributed to the energy dissipation of the column. Further study was carried out to investigate the seismic performance of the sliding-rocking columns under torsional and biaxial loading (Salehi et al 2021b).…”
Section: Rocking-sliding Column Systemmentioning
confidence: 99%
“…In 2009, Yamashita and Sanders (2009) conducted shake table tests on a 1/4 Fig. 8 Concept of sliding-rocking PSC (Salehi et al 2021b) scale PSC model on the shake table. The column had the geometry dimensions of 1016 mm × 457 mm × 2082 mm (length×width×height).…”
Section: Shake Table Tests On Pscsmentioning
confidence: 99%
“…Then, the set-up allows large-scale models to be tested on the shake table system. The large-scale samples can then be studied without compromising the safety of the shake table system 18 .…”
Section: Shaking Table (St) Testmentioning
confidence: 99%
“…Recently, more and more earthquake researchers have realized that the results, i. e., buildings' collapse resistance, are still quite skeptical after adopting the maximum considered earthquake (MCE) seismic design. Salehi et al 18 investigated the seismic performance of Second-Generation Hybrid sliding-rocking bridge columns through an extensive experimental study. The column specimen tested under combined lateral-torsional loading sustained minimal damage (i.e., sparse hairline cracks) under the peak drift ratios up to 2% (representing a 2475-year seismic hazard).…”
Section: Introductionmentioning
confidence: 99%
“…Results of shake table tests on a large-scale bridge specimen validated the use of this hybrid sliding–rocking concept to enhance the seismic performance of bridges (Sideris et al, 2014a, 2015). Design objectives and equations were also elaborated for this concept based on quasi-static lateral cyclic tests at large drift ratios (Salehi et al, 2021; Sideris et al, 2014b) and numerical studies (Salehi et al, 2017).…”
Section: Self-centering Rocking Systemsmentioning
confidence: 99%